The Effectiveness of Group Guidance Services in Reducing Students Cheating Behavior - Silfa Hafizah Pulungan*; Meilinda Meilinda (Riwayat: Educational Journal of History and Humanities, 2023)
Cheating is an act that reflects dishonest behavior, this is contrary to the goals of education in Indonesia which want every student to have the noble values of Pancasila which are reflected in his behavior. Related to this, one of the efforts made by the counseling teacher/counselor in reducing cheating behavior is by using group guidance services. This study aims to reduce students' cheating behavior by using quantitative research in the form of Pre-Experimental Design with The One Group Pretest Posttest Design. The population of this study were 264 students of class VIII MTs Al Ittihadiyah Pangkalan Masyhur Medan and the subjects of this study were 12 students based on the results of AUM PTSDL. In addition to reducing students' cheating behavior, the results of this study also aim to find solutions related to students' cheating behavior so as to help students master learning at school.